Integration Of AI Into Industry 4.0 To Address Challenges And Opportunities In The Packaging Industry - Solanki, Pranjal (Digital Repository of Theses, 2025)
The existing study aims to explore integration of AI into industry 4.0 to address challenges and opportunities in the packaging industry. The goals of the study is to identify and analyse factors affecting artificial intelligence adoption in the packaging industry in India; to examine the challenges of integrating artificial intelligence into industry 4.0 in the packaging industry in India; to examine the opportunities of integrating artificial intelligence into industry 4.0 in the packaging industry in India and to provide suitable recommendations to ensure effective adoption and integration of artificial intelligence into industry 4.0 in the packaging industry. The respondents for current study are employees from packaging industry of Small and Medium Sized Enterprises (SMEs) from India. The cities selected for survey from India are Bangalore, Delhi and Hyderabad. Therefore, Bangalore, Delhi and Hyderabad are universe for current research. In this study respondents are randomly selected using purposive sampling techniques. 600 employees from packaging industry from three distinctive cities of India are selected. The findings of challenges in AI integration in respondents’ organisation assessed and stated that poor IT infrastructural support delays the use of AI in the packaging plants is the key challenge. The results related to opportunities in AI integration in respondents’ organisation stated that AI-based predictive maintenance minimizes packaging-machinery downtimes is the opportunity the packaging industry look for. Lastly, recommendations for making AI adoption easy in respondents’ packaging organisation is assessed. The results of the study stated that implement pilot projects to receive the advantages of AI in practice during packaging is the key recommendation of the study. Keywords: artificial intelligence (AI), challenges, opportunities, packaging, Small and Medium Sized Enterprises (SMEs)